Modulation of Adjuvant Arthritis by Cellular and Humoral Immunity to Hsp65 - Kim, Eugene Y.; Durai, Malarvizhi; Mia, Younus; Kim, Hong R.; Moudgil, Kamal D. (Frontiers in Immunology, 2016)
Heat-shock proteins (Hsps) are highly conserved and their expression is upregulated in cells by heat and other stressful stimuli. These proteins play a vital role in preserving the structural and functional integrity of cells under stress. Despite the ubiquitous expression of Hsps in an individual, the immune system is not fully tolerant to them. If fact, Hsps are highly immunogenic in nature, and immune response to these proteins is observed in various inflammatory and autoimmune diseases. Studies on the immunopathogenesis of autoimmune arthritis in the rat adjuvant arthritis (AA) model of human rheumatoid arthritis (RA) as well as observations in patients with RA and juvenile idiopathic arthritis (JIA) have unraveled immunoregulatory attributes of self Hsp65-directed immunity. Notable features include protection against AA rather than disease induction following immunization of Lewis rats with self (rat) Hsp65; the diversification of T cell response to mycobacterial Hsp65 during the course of AA and its association with spontaneous induction of response to self Hsp65; the crossreactive T cells recognizing foreign and self homologs of Hsp65 and their role in disease suppression in rats; the suppressive effect of antibodies to Hsp65 in AA; and the use of Hsp65, its peptides, or altered peptide ligands in controlling autoimmune pathology. The results of studies in the AA model have relevance to RA and JIA. We believe that these insights into Hsp65 immunity will not only advance our understanding of the disease process in RA/JIA, but would also lead to the development of novel therapeutic approaches for autoimmune arthritis.